“DI BALIK JENGKELNYA JOKOWI” SEBUAH ANALISIS SEMIOTIK PROGRAM MATA NAJWA DI TRANS7 - Maulidatus Syahrotin Naqqiyah; Dwi Putri Robiatul Adawiyah; Dessy Dwi Lestari (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2020)
This research contains the analysis behind Jokowi's annoyance in the Mata Najwa program in Trans7. It was through the Mata Najwa television program that the various meanings of Najwa Shihab as the host of the Mata Najwa talk show brought several invited guests to discuss the intentions related to the President's anger. The theory used in this research is symbolic interaction theory related to symbolic meaning in the process of interaction between one individual and another. Then Roland Barthes' semiotic analysis is used to reveal the meaning of denotation, connotation and myth in the existing shows. The results showed that the president in his speech used a lot of diction choices which negated the existence of a warning for his ministers.